The Hydrosocial Cycle of the Atuel River in the Extractive Context (1987-2018) in Mendoza and La Pampa, Argentina - Langhoff, María Laura; Rosell, Patricia; Geraldi, Alejandra (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper aims to address, from the political ecology of water, the conflict between La Pampa and Mendoza Provinces, Argentina, over the Atuel River, before the onset of extractive activities such as fracking. We use the concept of hydrosocial cycle, which considers how society takes part in water circulation. The aim is to analyze the most significant events in the last 40 years of the hydrosocial cycle (1978–2018) and the proposals to settle the conflict. The method used is qualitative and starts by applying the Dagwood Sandwich method from historical geography, which addresses a central theme by periods. For data collection, we employ interviews and literature review. The results obtained help identify the extraordinary complexity of the extractive processes in the Atuel sub-basin and the participation of new agents such as transnational capital and socio-environmental committees. In conclusion, these provinces, especially La Pampa, need to consider new agents and actions linked to extractive activities and their influence on the conflict and its possible resolution.